SYNTHESIS, CRYSTAL-STRUCTURE AND PROPERTIES OF HG2BA2(Y,CA)CU2O8-DELTA - THE FIRST CUPRATE SUPERCONDUCTOR CONTAINING A DOUBLE MERCURY OXYGEN LAYER - Radaelli, P; Marezio, M; Tholence, J; Debrion, S; Loureiro, S; Santoro, A; Huang, Q; Capponi, J; Alariofranco, M; Chaillout, C (1994)
The first cuprate superconductor containing double (HgO)2 layers was synthesized using a high-pressure, high-temperature technique. The compound, with chemical formula Hg2Ba2Y1-xCaxCu2O 8-δ, contains a rock salt-type double HgO layer. The prototype compound Hg2Ba2YCu2O8-δ is an insulator. Superconductivity is induced in the system by partially replacing yttrium with calcium. © 1994.